KAJIAN ADAPTASI ENAM VARIETAS INHIBRIDA PADI RAWA (INPARA) PADA LAHAN SUB-OPTIMALDI DATARAN WAEAPO KABUPATEN BURU - M. P. Sirappa; Max L.J. Titahena (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
Assessment of six varieties of in-hybrid swamp rice (Inpara) adaptation at Debowae village, district Waeapo, Buru regency was conducted from September to December 2011. The assessment goal was to get 1 to 2 adaptive varieties with high productivity on sub-optimal land. The land area size used was 1 hectare. The assessment were done for six varieties namely Inpara 1 (V-1), Inpara         2 (V-2), Inpara 3 (V-3), Inpara 4 (V-4), Inpara 5 (V-5) and Indragiri (V-6). This research used a Randomized Block design replicated 3 times (farmers as replicates). Fertilizers used were 300 kg NPK Phonska ha-1, 200 kg urea ha-1 and 3 t of manure ha-1. Rice cultivating was done based on a model of integrated crop management (ICM). The whole amount of NPK Phonska fertilizer was applied 7 days after planting while urea fertilizer was given twice, half at 7 days after planting (dap), and the rest at 21 and 35 dap. Manure was spread on the plot before planting. Parameters measured were physical and chemical properties of soil, crop growth and yield components.       The study results showed that the type of soil at the study site was Endoaquepts with low soil fertility status. The six Inpara varieties are average provide higher productivity(4.87 to 7.95 t ha-1) compared with the average productivity advance (1-2 t ha-1) or grain yield obtained by farmers who plant varieties superior to the rice field (2.60 to 2.90 t ha-1). From the sixth varieties studied, four varieties of which provide results on the 7 t ha-1, which is Inpara 4 (7.95 t ha-1), Indragiri (7.75 t ha-1), Inpara 1 (7.44 t ha-1), and Inpara 2 (7.10 t ha-1), so the opportunity to developmenton the land       sub-optimal in the Moluccas, especially in the Buru plains Waeapo. Key Words : Adaptation studies, Buru plains Waeapo, inhibrida swamp rice (Inpara), land sub-optimal.